Biogeochemical Dynamics in Adjacent Mesoscale Eddies of Opposite Polarity. Issue 2 (6th February 2022) - Barone, Benedetto; Church, Matthew J.; Dugenne, Mathilde; Hawco, Nicholas J.; Jahn, Oliver; White, Angelicque E.; John, Seth G.; Follows, Michael J.; DeLong, Edward F.; Karl, David M.
Abstract: We examined the biogeochemical impact of paired mesoscale cyclones and anticyclones in spatial proximity (<200 km apart) in the North Pacific Subtropical Gyre. While previous studies have demonstrated that upwelling associated with the intensification of cyclonic eddies can supply nutrients supporting plankton productivity, we observed that steeper vertical gradients in inorganic nutrients increased nutrient fluxes due to diapycnal mixing during the mature stage of cyclonic eddies. The increased diapycnal nutrient supply was linked with expansion of eukaryotic phytoplankton biomass and intensification of the deep chlorophyll maximum (DCM) layer. This perturbation in the plankton community was associated with increased fluxes of biominerals (specifically particulate inorganic carbon and particulate silica) and isotopically enriched organic nitrogen in particles exported in the cyclone. The time‐integrated effects of thermocline vertical displacements on the lower euphotic zone were predictable deficits and surpluses of inorganic nutrients and dissolved oxygen, respectively. However, the stoichiometry of oxygen and inorganic nutrients differed from that predicted for production and consumption of phytoplankton biomass, requiring additional biological processes that decouple changes in oxygen and nutrient concentrations. The dynamics revealed by this study may be a common feature of oligotrophic ecosystems, where mesoscale biogeochemical perturbations are buffered by the DCM layer, which limits the ecological impact of eddies in the well‐lit, near‐surface ocean. Key Points: The steepness of the nutricline in mature mesoscale eddies is an important driver of variability in pelagic ecosystems Differences in eukaryotic phytoplankton communities alter the export of particulate inorganic carbon and particulate silica across eddies Relative changes in oxygen and nutrients linked to displacements of the thermocline reflect anomalous cycling of organic matter